Ecological Memories of Women in Nagaland and Northern Thailand. Issue 2 (December 2018) - Barooah, Samhita
This article is intended to reflect upon the intricacies of how women in Nagaland and in Northern Thailand are linked to their ecology. It is based on my doctoral work on women's memories of the ecological past in Nagaland and also on the fieldwork done during a summer school programme in Nong Tao village of Northern Thailand which establishes the connections between ecology and community. Naga women have contributed immensely towards seed-saving traditions, natural fibre weaving, dying, farming and horticulture. In Northern Thailand as well as Karen, women contribute immensely towards ecological regeneration. This article would reflect upon the experiences of women in rural livelihoods who manage to safeguard ecological resource, restore dying traditions and replenish everyday needs for their communities through the natural environment. Oral memories of women farmers about their ecological space transcend beyond territorial boundaries across villages, even sometimes historical events which get alive through their memories of the past. Such memories are sometimes personal with intricate collective connotations and sometimes public with contextual and personal implications.